Mendeteksi financial distress perusahaan sektor ritel go public di Indonesia menggunakan model grover - Miftahul Ihsan, Cahyo Randi; Hendrani, Ai (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Financial performance greatly determines the growth and development of a company. If financial performance declines, it can result in the company being in a state of financial distress. Financial distress is an early warning for companies before they are in a position of bankruptcy. The purpose of this study was to examine whether each variable in the Grover model can affect financial distress. The independent variables used in this study are Working capital to Total assets, Earnings before interest and taxes to Total assets, Return on Assets. This type of research is causality research with regression analysis and uses secondary data from the retail sector obtained on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. This study used 25 companies with a total data of 75 as data samples with the sample selection procedure carried out by applying the purposive sampling method. The results of this study indicate that the variables Working capital to Total assets, Earnings before interest and taxes to Total assets, Return on Assets simultaneously affect financial distress. The variables Working capital to Total assets and Earnings before interest and taxes to Total assets have a positive effect on financial distress, while Return on Assets has a negative effect on financial distress.